A hobbit, a wardrobe, and a great war : how J.R.R. Tolkien and C.S. Lewis rediscovered faith, friendship, and heroism in the cataclysm of 1914-1918 - Loconte, Joe, 1961- (Nashville, Tennessee : Nelson Books, an imprint of Thomas Nelson, 2015)
"The untold story of how the First World War shaped the lives, faith, and writings of J. R. R. Tolkien and C. S. Lewis"--Amazon.com.
The funeral of a great myth -- The last battle -- In a hole in the ground there lived a hobbit -- The lion, the witch, and the war -- The land of shadow -- That hideous strength -- Conclusion: The Return of the King.
Includes bibliographical references (pages 203-226) and index.
Keywords: Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation; Tolkien, J. R. R. -- 1892-1973 -- Religion; Lewis, C. S. -- 1898-1963 -- Criticism and interpretation; Lewis, C. S. -- 1898-1963 -- Religion; World War, 1914-1918.; Literature and society -- England -- History -- 20th century